Prediction of synergistic multi-compound mixtures: a generalized Colby approach - Soller, Henning; Soller, Annika (Crop protection, 2012)
The investigation of chemical mixtures used to cure plant diseases has a long history but is still a field of intensive research. Not just does one have to maximize the direct effect on the disease itself but one also has to take into account the adverse effects on consumer health, the development of multiple fungicide resistance and the fate of chemicals in the environment. So far theoretical modelling using Colby's formalism was limited to the simple comparison with experimental data to verify synergistic behaviour. However, a systematic experimental investigation of all possible combinations for multi-compound mixtures is a time consuming task. Facing ever more complex diseases we show how a generalized version of Colby's formula can be used as a predictive tool for synergistic multi-compound mixtures. We also demonstrate how to address the direct chemical effect and the adverse effects on consumer health on the same footing using this generalization of Colby's formalism. We relate this to a practical example by considering a multi-compound mixture used against grey mould.